MicroRNAs, cancer and ionizing radiation: Where are we? - Marta,Gustavo Nader (2015)
Summary The aim of this study is to describe the biogenesis of microRNA, its relations with carcinogenesis, and the correlation between microRNA and ionizing radiation (IR), focusing on radioresponsiveness. It is known that microRNA biogenesis is well established and involves different enzymatic cleavages, resulting in the production of mature microRNA. MicroRNAs are involved in carcinogenesis. Their interaction is related to the genetic and epigenetic changes associated with activation of proto-oncogenes or inactivation of tumor suppressor genes. Several studies have shown that the levels of expression of some microRNAs vary significantly after irradiation. There are evidences that microRNAs can influence cellular response after IR. In addition, microRNAs are related to modulation of the expression of several post-transcriptional targets in DNA damage response pathways, and to the DNA damage repair regulation mechanism. Future studies can clarify a possible clinical use of microRNAs as a new class of radiosensitive agents.